Analisis Kuantitatif Tentang Pengaruh Komunikasi Verbal Dan Nonverbal Dalam Proses Negosiasi Bisnis - Almadina Rakhmaniar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Communication is a crucial component in the business negotiation process. This study aims to analyze the influence of verbal and nonverbal communication on business negotiation outcomes, focusing on how much both types of communication contribute to negotiation success.This study uses a quantitative approach with a survey design. Data on verbal communication, nonverbal communication, and negotiation outcomes. Data were analyzed using multiple linear regression to evaluate the effect of the independent variables (verbal and nonverbal communication) on the dependent variable (negotiation outcome).The results of the analysis show that both verbal and nonverbal communication have a significant influence on negotiation outcomes. Verbal communication has a regression coefficient of 0.50 (t = 5.00, p < 0.01), while nonverbal communication has a regression coefficient of 0.40 (t = 3.33, p < 0.01). The coefficient of determination (R²) of 0.49 indicates that 49% of the variation in negotiation outcomes can be explained by these two variables. The F test yielded an F value of 46.56 (p < 0.01), indicating the overall significance of the model. The regression model used can explain 49% of the variation in negotiation outcomes, suggesting that these two types of communication should be considered to achieve successful negotiations. Other factors not included in this model also contribute to negotiation outcomes and could be the focus of further research.